The triangle of ICOs, Bitcoin and Ethereum: A time series analysis / Christian Masiak/Joern H. Block/Tobias Masiak/Matthias Neuenkirch - Christian Masiak; Jörn Hendrich Block; Tobias Masiak; Matthias Neuenkirch; Katja N. Pielen (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2018)
We analyse the triangle of Initial Coin Offerings (ICO) and cryptocurrencies, namely Bitcoin and Ethereum. So far, little is known about the relationship between ICOs, bitcoin and Ether prices. Hence, we employ both bitcoin and Ether prices but also the ICO amount to measure the future development of raised capital in ICOs. First, our results indicate that an ICO has an influence on the subsequent ICO. Second, not only bitcoin prices but also Ether prices play a considerable role with regard to the output of ICO campaigns. However, the effect of Ethereum is of shorter duration on ICO compared to Bitcoin on ICO. A further finding is that the cryptocurrency Bitcoin positively influences Ether. The implications of these findings for investors and entrepreneurial firms are discussed.
Keywords: G11; E22; M13; O16; 330; blockchain; cryptocurrency; entrepreneurial finance; initial coin offering; ICO